Effects of environmental pharmaceuticals on physiological parameters of marine mussels Mytilus galloprovincialis - Leopold, Viergine (2023)
The increasing consumption of pharmaceutical products is of environmental concern, as excreted parent compounds and their possibly active metabolites are not completely removed by wastewater treatment plants. Several studies have confirmed the occurrence of antidepressants in coastal waters in the ng/L concentration range. This research focuses on four antidepressants e.g. fluoxetine, FLX; sertraline, SERT; and citalopram, CITA (selective serotonin reuptake inhibitors, SSRIs) and venlafaxine, VEX (serotonin-norepinephrine re-uptake inhibitor, SNRI) and two metabolites norfluoxetine, NF and O-desmethylvenlafaxine, ODV, chosen because: serotonin and norepinephrine are the main invertebrate neuromodulators, thus changing their levels influences animal functions; antidepressants are among the top prescribed pharmaceuticals worldwide, biologically active at low concentrations with the potential to cause neuroendocrine disruption. This work aimed to observe difference in the toxicity among parent compounds, and the relative toxicity of metabolites. The effects have been measured on early life stages of Mediterranean mussel Mytilus galloprovincialis analyzing different end points after exposure to environmental concentration range (0.5 - 500 ng/L). SSRIs had greater effect on fertilization rate than SNRIs, with a similar effect by parent compound and metabolites. SERT caused the highest percentage of unfertilized eggs in a wide range of concentrations, from 10 ng/L to 500ng/L. The range of effect on embryo – larval development is as follows NF (5 -500 ng/L) > SERT (25-500 ng/L) > FLX (100-500 ng/L) > CITA (500 ng/L), while VEN and ODV were ineffective. Poor effects of antidepressants were observed on larvae motility and survival. In conclusion antidepressants and their metabolites affected mussel gamete fertilization and embryo development, thus representing a threat for the formation and maintenance of populations, disrupting the ecological system and biodiversity.